Ionic silver-infused peroxidase-like metal-organic frameworks as versatile "antibiotic" for enhanced bacterial elimination - Zhang, Wentao; Ren, Xinyi; Shi, Shuo; Li, Min; Liu, Lizhi; Han, Ximei; Zhu, Wenxin; Yue, Tianli; Sun, Jing; Wang, Jianlong (Nanoscale, 2020)
The fabrication of multiple antibacterial modalities for combating bacterial pathogens and treating infected wounds is of vital importance. Accordingly, nanozymes have emerged as a new generation of "antibiotics" with broad-spectrum antibacterial potency and high stability; however, the further application of nanozymes in clinical medicine is still limited by their single-modal antibacterial process, which cannot eradicate bacteria totally. Herein, we infused the NH 2 -MIL-88B(Fe) peroxidase-like nanomaterial with a small amount of Ag( i ) to construct NH 2 -MIL-88B(Fe)-Ag, a potent and benign "antibiotic" with the ability to eliminate bacteria completely. This versatile system could efficiently convert H 2 O 2 into the more toxic &z.rad;OH and release Ag( i ) simultaneously, making pathogenic bacteria more vulnerable to be eliminated, which decreased the requirement for the toxic H 2 O 2 and high concentration of Ag( i ). More importantly, the in vivo results indicated that the synergistic germicidal system could be used for wound disinfection successfully with excellent antibacterial efficacy and negligible biotoxicity. This strategy paves the way for the development of integrated antibacterial agents with enhanced antibacterial function and alternative antibiotics. A biocompatible ionic silver-metal organic framework composite with intrinsic peroxidase-like activity is successfully constructed for combating bacterial infection.